Refinement anomalous elevation EGM2008 base on GPS-levelling data in local region Tay Nguyen and south central coastal areas - Do, Nguyen Duy; Chinh, Dang Nam; Insisiengmay, Sisomphone (Vietnam Journal of Earth Sciences, 2012)
The paper introduces the process of refinement anomalous elevation EGM2008 base on GPS - Leveling data and Collocation method. Results show that the EGM08C improving Geoid ensure for determining leveling height by GPS on the Central Highland and Southcentral coastal areas with accuracy level equivalent  to IV-grade leveling assigned for mountainous area and achieved reliability of 100%. About 80% of which approached at III-grade leveling. Error of determined leveling height by GPS for over 1km reduces from 0,0244m/km to 0,009m/km (to 37%). Furthermore, the paper suggests employing the third-order Markov function as covariance, the Collocation method for data employed to improve Geoid model and to use the radius of the neighboring net points within a range from 6 to 10km.